In Pursuit of the Green Transition—Electricity at Any Cost? - Per Fahlén; Magnus Henrekson; Mats Nilsson (Institute of Labor Economics (IZA), 2025)
We examine EU and UK plans for achieving a fossil-free energy system by 2050, centered on massive electrification and large-scale deployment of wind and solar power. Using empirical trends, cost analyses, and system-function assessments, we argue that current strategies underestimate real economic, technical, and social challenges. Three scenarios for meeting 2050 electricity demand are compared: full reliance on renewables; a 50/50 split between wind-solar and nuclear; predominantly nuclear. Evidence shows that higher shares of weather-dependent generation correlate with higher electricity pric-es, greater volatility, and increased system integration costs. High renewable shares require extensive backup, storage, and grid reinforcement, raising complexity and environmental impacts. Overlooked costs are highlighted: reduced capacity value, transmission expansion, balancing services, and so-cial externalities. Sustainability must encompass environmental, economic, and social dimensions. A technologically diverse, dispatchable-power-based strategy—especially with expanded nuclear power— offers a more robust, cost-effective, and socially acceptable pathway to climate neutrality than a predominant reliance on intermittent renewables.
Keywords: L26; L52; L70; O38; P11; Q48; Q58; 330; climate change; cispatchable electricity; green transition; mission-oriented policy; renewable electricity; rent-seeking